2020
DOI: 10.1039/c9cp05634c
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic topological insulator MnBi2Te4: synthesis and magnetic properties

Abstract: Recently, MnBi2Te4 has been discovered as the first intrinsic antiferromagnetic topological insulator (AFM TI), and will become a promising material to discover exotic topological quantum phenomena. In this work, we have realized the successful synthesis of high-quality MnBi2Te4 single crystals by solid-state reactions. The as-grown MnBi2Te4 single crystal exhibits a van der Waals layered structure, which is composed of septuple Te-Bi-Te-Mn-Te-Bi-Te sequences as determined by powder X-ray diffraction (PXRD) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 42 publications
16
86
0
2
Order By: Relevance
“…Rapid and exciting experimental progress has been made in MnBi 2 Te 4 -family materials in the past years, constructing one of the hottest topics in condensed matter physics recently 8,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Single-crystal samples of MnBi 2 Te 4 -family materials have been successfully prepared by several groups [20][21][22][23][24][25][26][27] . The A-type AFM structure has been demonstrated with SQUID measurements and directly observed with magnetic force microscopy 28,29 .…”
Section: Research Progress On Mnbi 2 Tementioning
confidence: 99%
“…Rapid and exciting experimental progress has been made in MnBi 2 Te 4 -family materials in the past years, constructing one of the hottest topics in condensed matter physics recently 8,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Single-crystal samples of MnBi 2 Te 4 -family materials have been successfully prepared by several groups [20][21][22][23][24][25][26][27] . The A-type AFM structure has been demonstrated with SQUID measurements and directly observed with magnetic force microscopy 28,29 .…”
Section: Research Progress On Mnbi 2 Tementioning
confidence: 99%
“…ITO is highly water-resistant because one necessary step to clean ITO in solar cell fabrication process is immersing in water under ultrasonic. [9,30] The polymer ETLs adapted here are pBTTz and pBTT. Te is evaporated as an about 0.5 nm-thick discontinuous interlayer to increase the adhesion of Se films and serves as nucleation site for the t-Se.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that the performance of SSCs has been improved after a week, and the reason could be the strain releasing of Se polycrystalline films. [19,30] Ito et al reported that the efficiency of SSCs could keep increasing for 40 days due to releasing strains. [19] Todorov et al reported the fabricated SSCs could maintain the performance for more than half a year.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations